Two new species of bamboo-feeding leafhopper genus Flatfronta (Hemiptera, Cicadellidae, Deltocephalinae) from India - Meshram, Naresh M.; Nikoshe, Akash P.; Stuti, Stuti (Zootaxa, 2020)
Two new species of the bamboo-feeding leafhopper genus Flatfronta, F. dibangi sp. nov. (Arunachal Pradesh: Basar) and F. uttara sp. nov. (Uttarakhand: Pantnagar) are described and illustrated from India. A checklist and a key to known species of the genus are also provided. Types are deposited in the National Pusa Collection (NPC), Division of Entomology, ICAR-IARI, New Delhi, India.